Kepemimpinan Visioner; dalam Membangun Budaya Organisasi Berprestasi di MAN 2 Probolinggo - Sugianto, Muhammad (At- Ta'lim : Jurnal Pendidikan, 2018)
The birth of organizational culture in Islamic educational institutions can not be separated from the typology of visionary leadership. Organizations are therefore defined as a rational tool for coordinating and controlling a group of people in the process of achieving goals. Leadership appears in the process by which a person directs, guides, influences and or controls the thoughts, feelings and behavior of others. In the world of education, especially Islamic education, leadership in an Islamic educational institution has a strategic position in bringing Islamic educational institutions in the direction desired by a leader. Therefore, both the bad image of Islamic educational institutions is determined by both the poor performance, ability and image of a leader in managing the organization. In relation to the influence of the leadership of an Islamic educational institution-the head of a madrasah-, visionary leadership is needed as a requirement to create the effectiveness and efficiency of educational institutions, especially Madrasah Aliyah Negeri 2 Probolinggo, improving the quality of madrassas and forming the image of Islamic educational institutions. Keywords: Leadership Visionary and Organizational Culture